International trade and business law review - Jones, Roger; Moens, Gabrie¨l , 1948- (Routledge Cavendish, 2009)
Publishes leading articles, comments, case notes and book reviews dealing with international trade and business law, arbitration law, foreign law and comparative law. This title provides the legal and business communities with information, knowledge and understanding of developments in international trade and business